2017
DOI: 10.1111/grow.12220
|View full text |Cite
|
Sign up to set email alerts
|

“Bad Neighborhood” and Internet Adoption in Poor Countries: What is behind the Persistent Digital Gap?

Abstract: The paper investigates the determinants of Internet adoption in poor countries, focusing on the role of macro‐geographic location (neighborhood). It is argued that neighboring countries are interconnected by various kinds of spillovers, including knowledge spillovers as well as spillovers of norms and attitudes that affect individual adoption behavior. The empirical findings support the view that Internet adoption is affected by adoption rates in neighboring countries, even when controlling for a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The number in the category "economics" increased but fewer compared to "social" and "ICT," the latter being the most extensive group in the categories list. The growth of ICTs correlates closely with the digital transformation that the world has experienced in the last decade [18], which has aimed to answer emerging needs or perform operations more efficiently [17] (p. 124). The growth of topics and discussions about the digital gap highlights the interconnections and exponential impact in various contexts, levels, and dimensions; consequently, researchers must continue studies for justice and people's legitimate rights worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number in the category "economics" increased but fewer compared to "social" and "ICT," the latter being the most extensive group in the categories list. The growth of ICTs correlates closely with the digital transformation that the world has experienced in the last decade [18], which has aimed to answer emerging needs or perform operations more efficiently [17] (p. 124). The growth of topics and discussions about the digital gap highlights the interconnections and exponential impact in various contexts, levels, and dimensions; consequently, researchers must continue studies for justice and people's legitimate rights worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a 2019 study in the Netherlands, a country where 98% of the population has at-home internet access, the authors found that even there the impact of "age, gender, majority status, employment, education level, and household composition" [17] (p. 3069) contributed to a digital divide. In addition, lack of internet availability and disadvantaged geographic location [18] increase the gap for vulnerable groups. Thus, as the study concludes, an in-depth understanding of how companies adapt designs and strategies to face changes and challenges is urgent.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to western industrialized countries where innovation is more commonly applied, developing countries faced a slower rate of innovation adoption during the last period of the twentieth century (Zanello et al , 2016; Sabi et al , 2016). However, the portability and rapidly growing nature of information systems have resulted in an increasing rate of diffusion of innovation among those developing countries that support novel development strategies and can assist them in filling the digital gap between developing and developed countries (Newenham-Kahindi, 2015; Dohse and Lim, 2018). In addition, Newenham-Kahindi (2015) claimed that gaining the advantage of leapfrogging through using the strategies of technology transfer is not easy and accessible because of different existing obstacles.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%